PENGEMBANGAN LENDABOOK BERBASIS JEJARING SOCIAL NETWORK MENGGUNAKAN CAKEPHP - Bambang Sugiantoro; Ahmad Syarif Afandi (Jurusan Teknik Informatika, 2014)
Social network provides outstanding in effect current human life. relationship between human with other peopledo the easy. information about a person shall be easily obtained from the media is social network. this is noapart from the internet and computer technology development is rapidly increasing. reading is a need forcommunity. even reading this time as if being a new lifestyle in the community. this is visible from many visitorsbook stores and exhibition-book exhibition held in periodic. however, the amount of the enthusiastic with theability to buy book, especially for student or students. borrowing books are some of technology adoption forexisting problems. using the concept of social network using technology and internet. lendabook social networksite that is built for the purpose of sharing with facilitate the public in lend to each loan books.